Pleurotus eous polysaccharides suppress angiogenesis and induce apoptosis via ROS-dependent JNK activation and mitochondrial mediated mechanisms in MCF-7 human breast cancer cells (Bangladesh Journal of Pharmacology, 2015)
Breast cancer is one of the most prevalent cancers among women worldwide. Chemotherapy generally leads to drug resistance and severe side effects thus making it crucial to identify and develop highly efficient chemotherapeutic agents. Recently, edible mushrooms have been strongly investigated owing to their nutritional values and bioactive compounds with health benefits. The present study investigates the effects of polysaccharides isolated from the fruiting bodies of oyster mushroom, Pleutorus eous on MCF-7 human breast cancer cells. Viability of MCF-7 following exposure to P. eous polysaccharides (PEP) (50 - 250 µg/mL) were markedly decreased. A raise in the levels of Reactive Oxygen Species (ROS) and apoptotic cell counts were observed following PEP treatment. Futhermore, PEP down-regulated VEGF and Bcl-2 and raised caspase-3, caspase-9, Bax, phospho-JNK expressions and as well caused a significant decrease in mitochondrial membrane potential of MCF-7 cells. Thus, PEP effectively suppressed angiogenesis by down-regulating VEGF, and induced apoptosis.